2016
DOI: 10.1111/1750-3841.13369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carrageenan on Physicochemical and Functional Properties of Low‐Fat Colby Cheese

Abstract: The effect of carrageenan (κ-carrageenan, ι-carrageenan, and λ-carrageenan) on the physiochemical and functional properties of low-fat Colby cheese during ripening was investigated. Protein, fat, and moisture contents; the soluble fractions of the total nitrogen at pH 4.6; protein and fat recovery; and the actual yield and dry matter yield (DM yield) were monitored. Hardness, springiness, and the storage modulus were also evaluated to assess the functional properties of the cheese. Moreover, the behavior of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
2
15
0
1
Order By: Relevance
“…The average time required for the particles to travel a specific distance was longer over time, which was ascribed to constrained particle mobility due to gel formation . The addition of soymilk and TG decreased EI and storage modulus, which was related to lower interactions among proteins and a weakened network . Ion Titapiccolo, Corredig and Alexander, who studied the effects of non‐ionic surfactants on the renneting functionality of casein micelles, reported that the different storage modulus during renneting can be partly ascribed to differences in the release of caseinomacropeptides (CMPs) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The average time required for the particles to travel a specific distance was longer over time, which was ascribed to constrained particle mobility due to gel formation . The addition of soymilk and TG decreased EI and storage modulus, which was related to lower interactions among proteins and a weakened network . Ion Titapiccolo, Corredig and Alexander, who studied the effects of non‐ionic surfactants on the renneting functionality of casein micelles, reported that the different storage modulus during renneting can be partly ascribed to differences in the release of caseinomacropeptides (CMPs) .…”
Section: Discussionmentioning
confidence: 99%
“…Soy proteins have a higher water holding capacity than milk proteins . Therefore, soy proteins can promote the entrapment of moisture, similar to other hydrocolloids . Walstra, van Dijk and Geurts reported that the state of the casein network following gel formation is the most important factor that determines the moisture content of curds .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cheese analogue in this study included low-fat cheese, which has lower fat content compared to full-fat cheese (Wang et al, 2016). Based on wet weight, full-fat cheese in fresh form has a fat content of 24.5%.…”
Section: Characterization Of the Initial Productmentioning
confidence: 99%